A semântica das preposições pela ótica da ecolinguística - Simião, Lajla Katherine Rocha (2017)
Semantics has been considered, according to Couto (2007), as one of the least understood components of grammar. For this reason it has been treated in a hostile manner by some linguists, a fact that aroused the interest in researching it. Thus, we have two goals that will guide this research: firstly, to present the Semantics from the integrative approach proposed by Ecolinguistics. Therefore, we will depart from the spatial prepositions as they are represented in the Ecology of Spatial Relations, according to which all of them are reduced to spatiality, not only temporal prepositions, but also abstract or notional ones. We selected as object of analysis some compositions produced in the year 2015. Our theoretical basis is Ecolinguistics, which is the study of language interactions with the ecosystem, which can be natural, mental or social. To present Semantics from an ecological perspective we use as the main theoretical approach proposed by Couto (2007).